PENERAPAN METODE QUANTUM WRITER UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI PADA SISWA SMK TELEKOMUNIKASI DARUL’ULUM - Puteri, Dinike Agustin (sarasvati, 2019)
Quantum Writer method is good way to help student more easy and attractive to write. Quantum Writer method is contains four steps teaching learning writing ang can be easy to with PAK ! namely: concentrate (P), arrange (A), composing (K), the best (!). This method used to finished that problem appear (1) How to proces learning poerty at begining with Quantum Writer method, (2)   How to proces learning poerty when  student is writing poerty with Quantum Writer method, (3) How to proces learning poerty at the finishing or after writer poerty with Quantum Writer method, in this case every statement of the problem given student score. This Action Research (PTK) used descriptive kealitatif method is doing two steps is that observation student SMK Telekomunikasi Darul’Ulum. The data take from pre writing is contain students ability to mention theam. Then the result take from when student is writing poerty. With Quantum Writer merhod. Second step is that finished to write the result contains are reading a poerty, give suggestion with friend’s poetry, and revisi again based on friend’s  suggestion. The result of the observation is that appliying Quantum Writer writer method can be increase to writing poetry very good for student. Students ability to writing poetry more increase every steps. And the response of the student increase.